POLITIK DEMOKRASI PENDIDIKAN ISLAM (Dampak Politik Demokrasi Pendidikan Islam di Indonesia dan Malaysia terhadap Akses Layanan dan Mutu Pendidikan) - Muhammad Abdullah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2021)
How the political impact of Islamic education democracy in Indonesia and Malaysia on service access and quality of education. The method used in this research is library research. To collect data the author uses the documentation method. The data analysis technique used in this case is content analysis. Because the development of educational institutions cannot be separated from government policy factors as policy makers. How the policies formulated can advance education and provide access to quality education services and quality. Because education is the most influential sector in the progress of a country. The direction of the goal of national education is to develop a variety of human potential optimally so that an advanced civilizational order is formed in a nation. While Islamic education is part of the national education subsystem. Most Muslim-populated countries, such as Indonesia and Malaysia, Islamic education is an integral part of the nation which helped tread the nation's journey from the colonial period to the independence of the two countries. The role of Islamic education also colors how the democratic politics of education has an impact on the service access sector and the quality of education for the countries of Indonesia and Malaysia.